The knowledge and attitude of adults towards home safety measures of elders in Saudi Arabia - Daod, Abrar R.; Alhenaki, Reema A.; Alfaya, Raghad S.; Bakry, Huny M.; Aldawsari, Nada F. (International Journal Of Community Medicine And Public Health, 2023)
Background: The population of elderly individuals is increasing rapidly in the Kingdom of Saudi Arabia (KSA). Home safety measures are important for the well-being and independence of the elderly. However, little is known about the knowledge and attitudes of adults towards home safety measures of the elderly in KSA. Methods: This cross-sectional study was conducted in KSA among a sample of 399 adults aged 20 years and above. Data was collected using a designated questionnaire which was distributed through social media platforms. Results: The results showed that the overall knowledge of adults regarding home safety measures of the elderly in KSA was fair in 42% of participants and poor in 38% of participants. Moreover, the attitude of adults towards home safety measures of the elderly was positive in only 34 % of population. Conclusions: Knowledge and attitude regarding elderly home safety measures are significantly correlated and most of the participants demonstrated poor to fair knowledge. However, approximately half of the participants showed a neutral attitude regarding home safety measures towards elders.